(untitled) (De Legibus - Law Journal, 2022)
The paper pretends to briefly characterize the trial period and analyze the judgment of Constitutional Court nr. 318/2021 in the part that deals with the compliance of the amendments introduced by Law nr. 93/2019, issued on 4/09 to Portuguese Constitution, regarding the increase of trial period for first-time jobseekers and long-term unemployed persons.